Bacterially Delivered miRNA-Mediated Toll-like Receptor 8 Gene Silencing for Combined Therapy in a Murine Model of Atopic Dermatitis: Therapeutic Effect of miRTLR8 in AD - Wonsuck Yoon; Eun-Jae Kim; Yongsung Park; Seunghyun Kim; Yong-Keun Park; Young Yoo (Microorganisms, 2021)
In atopic dermatitis (AD), skin inflammation is caused by complex interactions between genetic disposition and aberrant innate/adaptive immune responses. Toll-like receptors (TLRs) are key molecules in the innate/adaptive immune response as they recognize various molecular motifs associated with pathogens. Among them, TLR8 is implicated in eczematous skin reactions. We investigated the combined therapeutic effects of TLR8 gene silencing by the bacterial delivery of miRNA. We used Salmonella as a vector to deliver TLR8 miRNA. The recombinant strain of Salmonella enterica subsp. enterica serovar Typhimurium (ST) expressing TLR8 miRNA (ST-miRTLR8) was prepared for knockdown of TLR8. After oral administration of ST-miRTLR8 into mice, we observed the cytokine levels, skin pathology and scratching behaviors in an AD-like mouse model. TLR8 down-regulation decreased macrophage-derived chemokine concentrations in activated human mast cells. Serum IgE and interleukin-4 production were suppressed whereas IFN-γ was induced after oral administration of ST-miRTLR8. Scratching behaviors and skin inflammation were also improved. In addition, attenuated S. typhimurium safely accumulated in mouse macrophages and showed adjuvant effects. This study shows that the recombinant miRNA that expresses the TLR8 miRNA has therapeutic effects by suppressing Th2 inflammation. TLR gene modulation using miRNA via Salmonella vectors will thus have a double-protective effect in the treatment of AD.